The “Muscles of the Psyche”: From Body Literacy to Emotional Literacy - Vulcan, Maya (Frontiers in Psychology, 2021)
Autism spectrum disorder (ASD) is a neuro-developmental condition, which requires a multi-disciplinary matrix of treatments, including functional, educational, and emotional interventions. The latter mode of treatment entails particular difficulties, inasmuch as the core deficits of this condition seem to challenge the very premises of traditional psychotherapy. Reciprocity, verbal and symbolic expression, and inter-subjective dynamics are often difficult to attain with clients diagnosed with ASD, and emotional treatment thus often turns out to be a frustrating process, which may well elicit questions as to the efficacy of psychotherapeutic emotional interventions. These core challenges, described in the literature, become particularly acute in view of the increasing number of clients diagnosed on the autistic spectrum in recent years, and the growing need for qualified therapists who have trained for working specifically with this condition. It seems, therefore, that it is high time for systematic research into the lived experience of therapists working with these clients in order to attain a better clinical and theoretical understanding of the condition itself and broaden the range of effective interventions. This study, informed by a phenomenological-hermeneutic approach which guided both the collection of data and its subsequent analysis, aims to address these issues by exploring the particular challenges faced by therapists in this field, the questions that come up in the process, modes of personal and professional coping, and the insights elicited by the therapeutic encounter. The research consisted of in-depth interviews with 28 practicing therapists from a broad range of clinical orientations, including Dance/Movement, Arts, Music and Drama therapists, clinical psychologists and clinical social workers. The essential themes that emerged from the participants’ responses and the analysis of the findings lend support to theoretical and developmental approaches which focus on the primacy and the foundational role of the concrete body in inter-subjective relationships and in the therapeutic process, and indicate the potential efficacy of somatic and kinetic interventions. The clinical implications of this study are thus highly relevant to the training and support of therapists working with ASD, who should be encouraged to develop greater receptivity to non-verbal modes of interaction in the therapeutic process.